Strain mapping of semiconductor specimens with nm-scale resolution in a transmission electron microscope. (January 2016) - Cooper, David; Denneulin, Thibaud; Bernier, Nicolas; Béché, Armand; Rouvière, Jean-Luc
Abstract : Highlights: Four different TEM-based techniques have been evaluated. DFEH can quickly map deformation with excellent precision. HAADF STEM can measure the deformation with best spatial resolution. NBED is easy to perform but can provide inaccurate results. N-PED provides best spatial resolution and sensitivity combined. Abstract: The last few years have seen a great deal of progress in the development of transmission electron microscopy based techniques for strain mapping. New techniques have appeared such as dark field electron holography and nanobeam diffraction and better known ones such as geometrical phase analysis have been improved by using aberration corrected ultra-stable modern electron microscopes. In this paper we apply dark field electron holography, the geometrical phase analysis of high angle annular dark field scanning transmission electron microscopy images, nanobeam diffraction and precession diffraction, all performed at the state-of-the-art to five different types of semiconductor samples. These include a simple calibration structure comprising 10-nm-thick SiGe layers to benchmark the techniques. A SiGe recessed source and drain device has been examined in order to test their capabilities on 2D structures. Devices that have been strained using a nitride stressor have been examined to test the sensitivity of the different techniques when applied to systems containing low values of deformation. To test the techniques on modern semiconductors, an electrically tested device grown on a SOI wafer has been examined. Finally a GaN/AlN superlattice was tested in order to assess the different methods of measuring deformation on specimens that do not have a perfect crystalline structure. The different deformation mapping techniques have been compared to one another and the strengths and weaknesses of each are discussed.